Re-Encryption with Attribute Key Management for Secure Transactions in Cloud (International Journal of Engineering and Computer Science, 2015)
Transferring of information to the cloud is valuable due to the access and adaptability of critical technical difficulties that are remain. Ensure sensitive information stored in the cloud from being detail and liberated by a cloud supplier that is fair yet curiosity. Novel adjustments to attribute based encryption are permitted to the approved clients to access the cloud information focused on the fulfillment of providing the services such that the higher computational burden from cryptographic operations is allocated to the cloud supplier and the aggregate expenses is brought down for the cloud clients. The cloud provider is to diminish the cost of client repudiation in a portable client environment while saving the security of client information stored in the cloud may alternatively perform information re-encryption. The protocol, which is realize on commercially popular cloud platforms to simulate real- world standards that show the efficiency of the scheme.